Suicide After Contact With Child and Adolescent Mental Health Services—A National Registry Study - Astrup, Helene; Myhre, Martin Ø.; Kildahl, Anine T.; Walby, Fredrik A. (Frontiers in Psychiatry, 2022)
Research has shown a strong association between suicide and mental disorders, and people in contact with services for mental health and substance use are known to be at high risk of suicide. Still, few studies have previously described suicide among young people in contact with Child and Adolescent Mental Health Services. The aim of this study is to examine the prevalence of contact and suicide rates by gender and age groups, and to describe patient demographics and service utilization in secondary mental health services. All young people in contact with Child and Adolescent Mental Health Services in the year prior to death in the period 2008–2018 were identified by linking the Norwegian Cause of Death Registry and the Norwegian Patient Registry. We estimated the prevalence of contact and suicide rates among those with and without contact, by gender and age groups. Characteristics of treatment contact were compared between boys and girls. Variables with significant differences were entered into a multivariate logistic regression model using gender as an outcome. More girls (39.7 %) than boys (11.8 %) had contact with Child and Adolescent Mental Health Services in the year prior to death. Among girls, suicide rates per 100,000 patients increased linearly in the age groups 10-13, 14-16 and 17-19 years: 5, 22 and 38 per 100,000 patients, respectively. Among boys, the suicide rate increased sharply from 7 per 100,000 patients in the age group 14-16 years to 40 per 100,000 patients in the 17-19-year-old group. In the age-adjusted multivariate model, boys were 4.07 (1.22–14.44, p=0.024) times more likely to have terminated contact at the time of death. This study shows gender differences in both suicide rates and service utilization among young people in contact with Child and Adolescent Mental Health Services before suicide, and future studies should focus on identifying the causes of these gender differences in service contact.